Perlindungan Hukum Folklore Dalam Hukum Kekayaan Intelektual Sebagai Pemanfaatan Potensi Daerah Demak - mastur, Mastur; Rahmawati, Rahmawati (LP2M, 2023)
The cultural diversity of Indonesia is well-known. Each region in Indonesia has its own folklore, which is derived from the local community. This folklore is known as folklore because it is primarily transmitted orally or through speech. The concept of individualistic and capitalistic western society does not allow (precludes) the protection of local communities' intellectual property rights, particularly their folklore, which is generally not owned individually by the members of the community in question (collectively). As a result, many incidents of misappropriation of Indonesian folklore works and their economic potential benefit foreigners more than indigenous peoples, as in the case of misappropriation of Sunan Kalijaga's folklore. The purpose of this study is to investigate the concept of protecting IPR against Sunan Kalijaga folklore in the context of optimal utilization of economic potential for the benefit of the local/customary community of Demak, as well as the obstacles encountered during the protection process. This study employs a normative juridical research method conducted through interviews, as well as a statutory approach to examine cases of rights abuse and commodification. The findings revealed that writing books and commodifying folklore into an electronic cinema based on folklore with the inclusion of the creator's name is not appropriate because folklore copyright is included as one of folklore and is owned by the state, in this case managed and represented by the government. The people who live in the area where the folklore originated have a moral and economic right to use the folklore. The Copyright Act does not adequately represent the related rights owned by the Demak local/customary community as a community of original stakeholders of Sunan Kalijaga folklore. This is due to the Copyright Act's still abstract arrangement of folklore, the characteristics of the community itself, which are communalistic and religious and do not understand IPR, and the ease with which foreigners can obtain Copyright protection for folklore works they publish. However, there are several protective mechanisms that can be used, including criminal law efforts, civil law, and documentation as a defensive measure. As a result, the government must educate the public about the significance of legal protection for folklore and revise the folklore regulation in the Copyright Act. Keywords: Folklore, indigenous peoples, Intellectual Property Rights AbstrakIndonesia dikenal dengan keanekaragaman budayanya. Setiap wilayah di Indonesia mempunyai cerita rakyat masing-masing yang berasal dari masyarakat daerahnya. Cerita rakyat ini pada dasarnya disebarkan melalui tutur kata atau lisan serta dikenal sebagai folkore. Konsep masyarakat barat yang individualistik dan kapitalistik tidak memungkinkan (preclude) untuk melindungi hak-hak dari masyarakat lokal atas kekayaan intelektual khususnya folklore mereka yang pada umumnya tidak dimiliki secara individual oleh anggota masyarakat yang bersangkutan (kolektif). Akibatnya, banyak terjadi peristiwa penyalahgunaan hak (misappropriation) atas karya-karya folklore Indonesia dan potensi ekonominya lebih banyak dinikmati oleh orang asing daripada masyarakat adat itu sendiri, seperti pada kasus misappropriation cerita rakyat Sunan Kalijaga. Bertujuan untuk mengkaji konsep perlindungan HKI terhadap folklore cerita rakyat Sunan Kalijaga dalam rangka pemanfaatan potensi ekonomi yang optimal bagi keuntungan masyarakat lokal/adat Demak serta kendala yang dihadapi dalam proses perindungan yang dilakukan. Penelitian ini menggunakan metode penelitian yuridis normatif, yang dilakukan dengan cara wawancara, dan menggunakan pendekatan perundang-undangan (statute approach) melihat kasus penyalahgunaan hak dan komodifikasi. Hasil penelitian menunjukkan bahwa Penulisan buku maupun komodifikasi cerita rakyat menjadi sinema elektronik yang berdasarkan cerita rakyat dengan pencantuman nama pencipta tidaklah tepat karena hak cipta atas cerita rakyat termasuk sebagai salah satu folklore serta dimiliki oleh negara, dalam hal ini dikelola dan diwakili oleh pemerintah. Masyarakat daerah asal cerita rakyat tersebut berada juga berhak atas pemanfaatan atas cerita rakyat tersebut, baik dari sisi hak moral dan hak ekonomi. Undang-Undang Hak Cipta belum cukup merepresentasi hak terkait yang dimiliki oleh masyarakat lokal/adat Demak sebagai komunitas pemangku asli folklore cerita rakyat Sunan Kalijaga. Hal ini disebabkan pengaturan folklore yang masih abstrak dalam Undang-Undang Hak Cipta, ciri masyarakatnya sendiri yang komunalistik dan religius serta tidak paham HKI dan mudahnya orang asing memperoleh perlindungan hak cipta atas karya folklore yang dipublikasikannya. Walaupun demikian ada beberapa mekanisme perlindungan yang dapat diterapkan, yakni upaya hukum pidana, hukum perdata, tindakan dokumentasi sebagai sarana defensive protection. Oleh karena itu, Pemerintah perlu melakukan sosialisasi mengenai pentingnya perlindungan hukum atas folklore serta mengkaji ulang pengaturan folklore di dalam Undang-Undang Hak Cipta. Kata Kunci: Folklore, masyarakat adat, Kekayaan Intelektual